OVERVIEW OF GMP INSPECTIONS RESULTS OF FOREIGN MANUFACTURING SITES IN 2017 - V. A. Orlov (Разработка и регистрация лекарственных средств)
The matter presents the analysis of results for GMP inspections of foreign manufacturing sites in 2017 and gives the comparison of them with the results from 2016. Statistical evaluation of the results obtained is also given. In comparison with the corresponding results from 2016, there is a significant increase in the total number of inspections conducted. The changes also reflected in the percentage of discovered GMP non-conformities both in terms of criticality and in the categories of good manufacturing practices. The article also presents some examples of discovered GMP non-conformities.